Antara Idealita dan Realita: Analisis Literatur tentang Kesiapan Guru dalam Menerapkan Pembelajaran Berdiferensiasi - Devi Mayanti Magdalena Manullang; Budiaman; Achmad Nur Hidayat (PT. Penerbit Tiga Mutiara, 2025)
Differentiated Instruction (DI) has become a pedagogical approach promoted in the Independent Curriculum (Curriculum Merdeka) as a strategy to address the diverse learning needs of students. However, implementation in the field shows a gap between the expected ideals and the realities faced by teachers. This gap between ideals and realities in the field is one of the issues that needs to be researched and assessed so that teachers' readiness as differentiated learning instructors receives attention and can be improved. This study aims to analyze literature related to teacher readiness in implementing differentiated learning in Indonesia. This study uses a literature review approach by reviewing 10 relevant national journals. The 10 national journals represent the results of research conducted in various schools in Indonesia, where these schools have implemented differentiated learning. The results of this descriptive research indicate that most teachers are still in the early stages of understanding differentiated learning and face implementation challenges that include limited training, homogenous learning needs, and suboptimal system support. Thus, the need for teacher readiness in implementing differentiated learning is still far from optimal. In this case, not only teachers are required to be able to carry out their duties in implementing differentiated learning optimally, but related parties in the education sector should also contribute significantly to promoting teacher readiness. The definition of readiness is not only focused on teachers, but as teachers carry out their primary duties as educators, primary readiness is the foundation that teachers must possess. Therefore, a redefinition of the meaning of teacher readiness is needed, which is not only seen from the aspect of individual abilities, but also as part of an educational system that supports structurally, culturally, and professionally.